2018
DOI: 10.1111/bph.14447
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of nitrergic neurotransmission in the bed nucleus of the stria terminalis in controlling cardiovascular responses to emotional stress in rats

Abstract: These results indicate that inhibitory control of stress-evoked cardiovascular responses by nitrergic signalling in the BNST is mediated by a facilitation of local noradrenergic neurotransmission. The present data also provide evidence of an involvement of local nNOS in facilitatory control of tachycardia during stress by NMDA receptors within the BNST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Activation of the NMDA glutamatergic receptor in postsynaptic neurons results in NO formation through a Ca +2 -dependent mechanism and activation of the nNOS (Chachlaki and Prevot, 2019; Garthwaite, 2008, 2019). Accordingly, we recently reported that the facilitatory influence of the NMDA receptor within the BNST in stress-evoked cardiovascular responses is mediated by local nNOS activation (Barretto-de-Souza et al, 2018). Although these pieces of evidence, the endocannabinoid-glutamate neurotransmission interaction was never explored in terms of an involvement of NO signaling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Activation of the NMDA glutamatergic receptor in postsynaptic neurons results in NO formation through a Ca +2 -dependent mechanism and activation of the nNOS (Chachlaki and Prevot, 2019; Garthwaite, 2008, 2019). Accordingly, we recently reported that the facilitatory influence of the NMDA receptor within the BNST in stress-evoked cardiovascular responses is mediated by local nNOS activation (Barretto-de-Souza et al, 2018). Although these pieces of evidence, the endocannabinoid-glutamate neurotransmission interaction was never explored in terms of an involvement of NO signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this experiment was to investigate the involvement of local NMDA glutamate receptor, nNOS, sGC, and PKG in control of the cardiovascular responses to acute restraint stress by the CB 1 receptor within the BNST. For this, independent sets of rats were pretreated into the BNST with either the selective NMDA receptor antagonist LY235959 (0.5 nmol/100 nL), the selective nNOS inhibitor NPLA (0.2 nmol/100 nL), the sGC inhibitor ODQ (0.5 nmol/100 nL), the selective PKG inhibitor KT5823 (0.01 nmol/100 nL/side), or vehicle (saline or DMSO 20%, 100 nL/side) (Barretto-de-Souza et al, 2018; Oliveira et al, 2018). Five minutes later, the animals received either vehicle (DMSO 20%, 100 nL/side) or AM251 (100 pmol/100 nL) into the BNST (Gomes-de-Souza et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adami et al (2017) showed that, after restraint, BNST glutamatergic neurotransmission in rodents influences changes in heart rate and tail skin temperature via co-activation of N-Methyl-D-aspartate (NMDA) and non-N-Methyl-D-aspartate (NMDA) receptors. Several studies have also demonstrated an involvement of CRF1 and CRF2 receptors (Oliveira et al, 2015), α1-adrenoceptors (Barretto-de-Souza et al, 2018), and endocannabinoid CB1 receptors (Gomes-de-Souza et al, 2016) in the BNST in cardiovascular adjustments during restraint stress (Oliveira et al, 2015). However, PVN CRF mRNA is not upregulated following restraint stress (Stroth et al, 2011) indicating upstream activation of CRF function ( via PACAP, for example; Hammack et al, 2010; King et al, 2017b).…”
Section: Animal Models Of Ptsdmentioning
confidence: 99%